Detection of the ORF1 Gene Is an Indicator of the Possible Isolation of Severe Acute Respiratory Syndrome Coronavirus 2 - Shirato, Kazuya; Kakizaki, Masatoshi; Tomita, Yuriko; Kawase, Miyuki; Takeda, Makoto (Pathogens (Basel), 2022)
In the ongoing coronavirus diseases 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), real-time RT-PCR based diagnostic assays have been used for the detection of infection, but the positive signal of real-time RT-PCR does not necessarily indicate the infectivity of the patient. Due to the unique replication system of the coronavirus, primer/probe sets targeted nucleocapsid (N) and spike (S) protein detect the abundantly synthesized subgenomic RNAs as well as the virus genome, possibly making the assay unsuitable for estimation of the infectivity of the specimen, although it has an advantage for the diagnostic tests. In this study, the primer/probe set targeting the open reading frame 1a (ORF1a) gene was developed to specifically detect viral genomic RNA. Then the relation between the ORF1a signal and infectivity of the clinical specimens was validated by virus isolation using VeroE6 cells, which constitutively express transmembrane protease, serine 2, (VeroE6/TMPRSS2). The analytical sensitivity of developed ORF1a set was similar to that of previously developed N and S sets. Nevertheless, in the assay of the clinical specimen, detection rate of the ORF1a gene was lower than that of the N and S genes. These data indicated that clinical specimens contain a significant amount of subgenomic RNAs. However, as expected, the isolation-succeeded specimen always showed an RT-PCR-positive signal for the ORF1a gene, suggesting ORF1a detection in combination with N and S sets could be a more rational indicator for the possible infectivity of the clinical specimens.